1983
DOI: 10.1111/j.1399-3054.1983.tb05734.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of ATPase from sugarcane protoplast and vacuole membranes

Abstract: Characteristics of membrane‐associated ATPase from commercial Hawaiian varieties of sugarcane (Saccharum spp. hybrids) were investigated in preparations from sugarcane cell suspension culture and from stalk tissues of the intact plant. In order to examine comparable preparations, protoplasts and vacuoles, in turn, were obtained from both sources. ATPase from preparations of crude protoplast membranes and tonoplast had a pH optimum of 6 to 6.5. The relative effectiveness of divalent cations in stimulating ATPas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Vanadate, an inhibitor of plasma membrane ATPase, was without effect . ATPase activities have also been demonstrated in vacuoles from Hevea latex [10], Hippeastrum and Tulipa vacuoles [22,36] and sugarcane suspension cells [32] . Thus despite early doubts [6] there now seems good evidence that the tonoplast does possess ATPase activity .…”
Section: Transport Of Sucrose Into Vacuolesmentioning
confidence: 98%
“…Vanadate, an inhibitor of plasma membrane ATPase, was without effect . ATPase activities have also been demonstrated in vacuoles from Hevea latex [10], Hippeastrum and Tulipa vacuoles [22,36] and sugarcane suspension cells [32] . Thus despite early doubts [6] there now seems good evidence that the tonoplast does possess ATPase activity .…”
Section: Transport Of Sucrose Into Vacuolesmentioning
confidence: 98%
“…Vacuoles isolated from sugarcane cells grown in suspension culture hydrolysed ATP (Thom et al 1983;Thom and Komor 1984a) and transported 3-OMG against a concentration gradient (Thom et al 198227). These results indicated that sugarcane has a tonoplast-bound ATPase that translocates protons into the vacuole thereby generating the ;+ H+ H+ proton gradient (Thom and Komor 1985) needed for operating a hexose H+-antiport system ([3] of Fig.…”
Section: Membrane Transportmentioning
confidence: 99%
“…These isolated vacuoles hydrolyze ATP (23,24) and transport sugars against a concentration gradient (22 (11), but the value is close to zero when measured as the accumulation of thiocyanate (24). Both values must be regarded with caution since it is difficult to correct for a significant amount of probe adsorption.…”
mentioning
confidence: 99%